Crise climática e audiovisual : representações da realidade na ficção - Lima, José Bonifácio de Andrade (2022)
Climate change has been worrying the world for a long time and even with the matter being urgently treated by the scientific community, many people still insist on ignoring the notable signs and impacts of the resulting climate crisis: melting glaciers, forest fires, rising of the average global temperature, etc. With that in mind, the present research aims to carry out an analysis of how the climate crisis is approached in highly-circulated and successful films, questioning the films “The day after tomorrow” (2004); “Avatar” (2009) and “Snowpiercer” (2013) their approaches to climate change and environmental guidelines, aiming to identify and analyze the representations contained therein, seeking to establish a relationship between the climate crisis and pop culture, pointing out its role as a vehicle for discussing the issue. To do so, we set our theoretical bases on Ecosocialism, a discussion developed by Löwy (2014), in addition to using concepts such as pop culture, presented by Zeisler (2008), drawing a parallel with authors of Social Communication who propose consonant ideas, such as Canclini (1997) and Kellner (2001); We also bring to the discussion terms such as climate change, which covers the exploitation of natural resources, highlighting deforestation in the global scenario and in the Amazon, thus proposing a dialogue between authors such as Hansen (2013), Marques (2018), Silva and Ravena ( 2015). We emphasize that the choice of the three cinematographic works mentioned fell on the potential for analysis, although their plots may not be centered on the climate issue, being also taken in consideration the fact that they are highly successful films and broadcast on several platforms and are works that make use of different narrative forms and aesthetic resources.